2021
DOI: 10.1016/j.biopha.2021.112230
|View full text |Cite
|
Sign up to set email alerts
|

Metformin to decrease COVID-19 severity and mortality: Molecular mechanisms and therapeutic potential

Abstract: The COVID-19 pandemic caused by the coronavirus SARS-CoV-2 has become a serious challenge for medicine and science. Analysis of the molecular mechanisms associated with the clinical manifestations and severity of COVID-19 has identified several key points of immune dysregulation observed in SARS-CoV-2 infection. For diabetic patients, factors including higher binding affinity and virus penetration, decreased virus clearance and decreased T cell function, increased susceptibility to hyperinflammation, and cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 153 publications
0
38
0
Order By: Relevance
“…Raptor subunit in mTORC1 is found to be sensitive to rapamycin and is thus inhibited by it, while Rictor subunit of mTORC2 is rapamycin-insensitive and therefore not inhibited by rapamycin. The rapamycin-sensitive mTORC1 has a key role in protein synthesis, cell growth, and so on and the rapamycin-insensitive mTORC2 is mostly involved in cell survival and cytoskeletal organization [27].…”
Section: Sars-cov-2 and Mtor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Raptor subunit in mTORC1 is found to be sensitive to rapamycin and is thus inhibited by it, while Rictor subunit of mTORC2 is rapamycin-insensitive and therefore not inhibited by rapamycin. The rapamycin-sensitive mTORC1 has a key role in protein synthesis, cell growth, and so on and the rapamycin-insensitive mTORC2 is mostly involved in cell survival and cytoskeletal organization [27].…”
Section: Sars-cov-2 and Mtor Pathwaymentioning
confidence: 99%
“…Therefore, it can be helpful in the treatment of COVID-19. Recent retrospective studies suggest metformin as an effective pharmacological treatment in COVID-19 patients based on data on SARS-CoV-2 patients with diabetes mellitus [27]. Metformin inhibits mTORC1 by AMPK phosphorylation and activation via activating liver kinase B1 (LKB1).…”
Section: Metformin Tacrolimus Sapanisertib and Pp-242: Mtor Inhibitorsmentioning
confidence: 99%
“…Akkermansia muciniphila is one of the well-known utilizers of mucin, which is decreased in patients with diabetes, obesity, and cardiovascular disease not treated with metformin. It plays a vital role in maintaining intestinal mucosa integrity, reducing the migration of pro-inflammatory LPS, and improving blood glucose levels [ 141 , 142 , 143 , 144 ]. Another clinical study of 27 healthy young adults (the participants were given metformin up to 1g twice daily) found that metformin reduced Clostridium spp.…”
Section: Immunoregulation Gut Microbiota and Covid-19mentioning
confidence: 99%
“…Thus, metformin may decrease the ACE2 binding ability of SARS-CoV-2 as well as increase the expression and stability of ACE2 through activating AMPK. Metformin can also be involved in the development of COVID-19 by inhibiting the mTOR signaling pathway [ 40 , 41 ] and altering the composition of the gut microbiota [ 42 ]. A recent study showed users of metformin had few adverse outcomes compared to nonusers [ 43 ].…”
Section: Discussionmentioning
confidence: 99%